A Significance of Human Rights - Dr. S. M. Jadhav , (International Journal of Research in Informative Science Application & Techniques (IJRISAT), 2022)
The present day human rights advocacy can be justified on grounds of ‘positive view of freedom’. This entails ‘the view that individual freedom in the full sense involves having an opportunity for self- realization... The political content of the positive view is that, if certain resources, powers or abilities are needed for self-realization to be effectively achievable, then having these resources must be considered part of freedom itself. It is on this basis that modem revisionary liberals have defended the welfare state as a freedom- enhancing institution: it is alleged to confer needed resources on individuals and thereby to expand their chances of freedom’.( Gray.l986:pp.57,58). The view of Bentham on natural rights and the statement of Maurice Cranston on human rights sets in motion the contemporary debate on human rights. On natural rights Bentham opined that “Right is the child of law; from real laws come real rights, but from imaginary law, from “laws of nature”, come imaginary rights...Natural rights is simple nonsense,, natural and imprescriptibly rights...rhetorical nonsense, nonsense upon stilts’.(Quoted in Cranston, Maurice 1967:p.44). According to Maurice Cranston, “The traditional human rights are political and civil rights such as the right to life, liberty and a fair trial. What are now being put forward as universal human rights human rights are social and economic rights such as the right to unemployment insurance, old-age pensions, medical services and holidays with pay. I have both a philosophical and political objection to this. The philosophical objection is that the new theory of human rights does not make sense. The Political objection is that the circulation of a confused notion of human rights hinders the effective protection of what are correctly seen as human rights.(Ibid.p.43). The views expressed by Cranston appealed to me as relevant on perusal of the Vienna declaration and Programme of action adopted by the World Conference on Human rights in Vienna on 25 June 1993.